Back Cover: Gene Fusion and Directed Evolution to Break Structural Symmetry and Boost Catalysis by an Oligomeric C−C Bond‐Forming Enzyme (Angew. Chem. Int. Ed. 8/2022). Issue 8 (18th January 2022) - Xu, Guangcai; Kunzendorf, Andreas; Crotti, Michele; Rozeboom, Henriëtte J.; Thunnissen, Andy‐Mark W. H.; Poelarends, Gerrit J.
Abstract : Gene fusion is an important natural process to create new enzymes from simpler ancestors. Gerrit J. Poelarends and co‐workers have adopted this strategy in their Communication (e202113970) to evolve a promiscuous homohexameric 4‐oxalocrotonate tautomerase (4‐OT) into an efficient enzyme for enantioselective Michael reactions. They designed a tandem fused 4‐OT that has reduced structural symmetry, expanding its optimization potential by allowing independent sequence diversification of adjacent subunits, and thus enlarging the protein sequence space that can be travelled by directed evolution.